2022
DOI: 10.19105/ghancaran.vi.7447
|View full text |Cite
|
Sign up to set email alerts
|

Citra Kurikulum Baru: Kesiapan Guru dalam Menerapkan Kurikulum Merdeka

Abstract: Guru dituntut untuk memiliki kompetensi pedagogik dengan menerapkan kurikulum yang sedang berlaku. Akan tetapi, guru belum menerapkan kurikulum tersebut, tetapi sudah diminta menerapkannya dalam Program Profesi Guru Dalam Jabatan (PPG Daljab). Berdasarkan hal itu, penelitian ini bertujuan mendeskripsikan pengalaman mahasiswa PPG Daljab dalam menerapkan Kurikulum Merdeka. Metode penelitian ini adalah narrative inquiry. Subjek penelitian adalah lima mahasiswa PPG Daljab Universitas Muhammadiyah Malang. Hasil pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
0
6
0
8
Order By: Relevance
“…However, the growth mindset is still not widely used in school curriculums. The present curriculum requires teachers to have pedagogical competency [57]. Teachers must understand and implement curriculum changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the growth mindset is still not widely used in school curriculums. The present curriculum requires teachers to have pedagogical competency [57]. Teachers must understand and implement curriculum changes.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, teachers can facilitate learning that promotes student competence [58]. Previous research found that teacher interventions were less significant than student interventions [10] because of substantial and technical obstacles, which teachers can overcome by continuing to investigate knowledge and gaining experience through practice [57].…”
Section: Discussionmentioning
confidence: 99%
“…Perubahan Kurikulum 2013 (K-13) menjadi Kurikulum Merdeka perlu diiringi dengan penyiapan peserta didik untuk terbiasa menggunakan Bahasa Inggris, karena di K-13 tidak ada pembelajaran Bahasa Inggris (Karimah & Al-Nur, 2023). Beberapa hasil penelitian juga menemukan jika guru belum cukup siap untuk beralih, karena kurangnya pemahaman dan kurang adanya pelatihan yang utuh untuk mendalami Kurikulum Merdeka (Oktaviani & Ramayanti, 2023;Prihatini & Sugiarti, 2022;E. Y. Rahayu et al, 2022;Tari et al, 2022).…”
Section: Pendahuluanunclassified
“…Fenomena serupa juga diungkapkan oleh guru pamong praktikan SMK Akuntansi yang ada di Kota Malang, bahwa praktikan kurang siap jika diminta mempersiapkan perangkat ajar berbasis Kurikulum Merdeka. Bahkan mahasiswa PPG Dalam Jabatan, yang memiliki latar belakang guru, merasa lebih siap menerapkan Kurikulum Merdeka setelah mengalami fase praktik pengalaman lapangan (Prihatini & Sugiarti, 2022).…”
Section: Pendahuluanunclassified
“…Based on research conducted by (Prihatini 2022) the implementation of the independent curriculum encourages teachers to continue to innovate in learning in terms of planning, implementing, evaluating, and following up. Independent curriculum or independent learning is freedom of thought.…”
Section: Introductionmentioning
confidence: 99%